Health norms in pregnancy. Issue 1 (March 1977) - Barić, L; MacArthur, C
Abstract : A study was conducted on a sample of pregnant women. The study had two aims: to develop a method of measuring social expectations (norms) and to find out how far women conform in their behaviour to these norms. The areas of behaviour were smoking, exercise, diet, alcohol, and medication. Pregnancy was found to be appropriate for this study because of the high degree of formalisation that this state enjoys in our society. The methods used for measuring norms in this study are an improvement on earlier methods, but further refinements are needed. The findings show that women generally do conform to the social expectations and that their behaviour is in accordance with three types of norms–that is, general, specific, and transitional. The implications for health education interventions are discussed.